Through your eyes: incongruence of gaze and action increases spontaneous perspective taking - Furlanetto, Tiziano; Cavallo, Andrea; Manera, Valeria; Tversky, Barbara; Becchio, Cristina (Frontiers in Human Neuroscience, 2013)
What makes people spontaneously adopt the perspective of others? Previous work suggested that perspective taking can serve understanding the actions of others. Two studies corroborate and extend that interpretation. The first study varied cues to intentionality of eye gaze and action, and found that the more the actor was perceived as potentially interacting with the objects, the stronger the tendency to take his perspective. The second study investigated how manipulations of gaze affect the tendency to adopt the perspective of another reaching for an object. Eliminating gaze cues by blurring the actor’s face did not reduce perspective-taking, suggesting that in the absence of gaze information, observers rely entirely on the action. Intriguingly, perspective-taking was higher when gaze and action did not signal the same intention, suggesting that in presence of ambiguous behavioral intention, people are more likely take the other’s perspective to try to understand the action.